2007
DOI: 10.1111/j.1745-6916.2007.00029.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Treatments That Cause Harm

Abstract: The phrase primum non nocere (“first, do no harm”) is a well-accepted credo of the medical and mental health professions. Although emerging data indicate that several psychological treatments may produce harm in significant numbers of individuals, psychologists have until recently paid little attention to the problem of hazardous treatments. I critically evaluate and update earlier conclusions regarding deterioration effects in psychotherapy, outline methodological obstacles standing in the way of identifying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
612
1
36

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 774 publications
(673 citation statements)
references
References 123 publications
7
612
1
36
Order By: Relevance
“…PTSD trials were by far most likely to include harmrelated data. There are two plausible reasons for this: First, within the field of trauma several well-known ineffective and potentially harmful treatments have been and still are used [5], which probably have increased the sensitivity for…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PTSD trials were by far most likely to include harmrelated data. There are two plausible reasons for this: First, within the field of trauma several well-known ineffective and potentially harmful treatments have been and still are used [5], which probably have increased the sensitivity for…”
Section: Discussionmentioning
confidence: 99%
“…Although an increasing number of RCTs show that psychological interventions can be successfully applied to a wide range of mental disorders [3,4], less is known about potential harms (i.e., adverse events, side effects, and symptom deterioration). However, some psychological treatments might induce harm in a significant number of patients [5][6][7][8]. A review from 2007 lists some bona fide therapies that are potentially harmful, such as critical incident stress debriefing, grief counseling for normal bereavement, and boot camp interventions for conduct disorder [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have suggested that DD treatment is harmful (Lambert & Lilienfeld, 2007; Lilienfeld, 2007); if this viewpoint is accurate, specialized treatment would likely also increase the economic burden of DD patients on the health care system. This is an important area that merits more research.…”
Section: Highlightsmentioning
confidence: 99%
“…Un problema metodológico importante es que gran parte de los estu dios solo compara a los pacientes que han finalizado el tratamiento y desechan a los que lo abandonaron. La débil alianza tera péutica es un buen predictor de abandono y en sí misma es un indicador o una con secuencia de una terapia fallida 82 .…”
Section: Iatrogenia Y Prevención Cuaternaria En Salud Mentalunclassified